2016
DOI: 10.1002/1873-3468.12202
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of hepatitis B virus entry – novel tools and approaches to directly follow virus entry into hepatocytes

Abstract: Hepatitis B virus (HBV) is a widespread human pathogen, responsible for chronic infections of ca. 240 million people worldwide. Until recently, the entry pathway of HBV into hepatocytes was only partially understood. The identification of human sodium taurocholate cotransporting polypeptide (NTCP) as a bona fide receptor of HBV has provided us with new tools to investigate this pathway in more details. Combined with advances in virus visualization techniques, approaches to directly visualize HBV cell attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…Finally, the cells allow visualization of viral replication and assembly, e.g. by FISH for genomic or antigenomic viral RNA or by fluorescent labeling of the HDAg using amber technology and click chemistry as described for the HBV capsid 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cells allow visualization of viral replication and assembly, e.g. by FISH for genomic or antigenomic viral RNA or by fluorescent labeling of the HDAg using amber technology and click chemistry as described for the HBV capsid 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in imaging technologies can visualise the internalisation of virus particles (reviewed in [Wang, Burckhardt, Yakimovich, & Greber, 2018]). Several studies have reported the use of fluorescent labelled HBV viral structural proteins or sub‐viral particles (Hao et al, 2011; Zhang et al, 2016). However, these approaches come with certain constraints as the labelling can impair viral infectivity and do not always resemble natural infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in imaging technologies can visualise the internalization of virus particles (reviewed in 47 ). Several studies have reported the use of fluorescent labelled HBV viral structural proteins or sub-viral particles 17,48 .…”
Section: Discussionmentioning
confidence: 99%